Structural, magnetic, multiferroic and electronic properties of sr2timno6 double perovskite (2012)
We report structural analysis, magnetic ordering, ferroelectric behavior and electronic structure of Sr2TiMnO6 complex perovskite. Samples were produced by the solid state reaction recipe. Crystallographic analysis was performed by Rietveld refinement of experimental x-ray diffraction patterns. Results show that this material crystallizes in a perovskite tetragonal structure which corresponds to the space group I4/mmm. We obtain a matching of 99 % between structural properties predicted by Density Functional Theory and structural ordering, found from the Rietveld refinement method. From Field Cooling measurements of susceptibility as a function of temperature, we determine the occurrence of a magnetic ordering for a critical temperature of 44.8 K. From the fitting with the Molecular Field Theory of ferrimagnetism we establish that the ordering corresponds to a paramagnetic-ferrimagnetic transition, which is corroborated by the behavior of the inverse of susceptibility as a function of temperature. The Curie constant permitted to obtain an effective magnetic moment of 3.5 uB. The result of magnetization as a function of applied field, measured at T=40 K, shows a ferromagnetic-hysteretic behavior. The curve of polarization as a function of applied voltage evidences a ferroelectric character. It is experimentally showed that below 44.8 K this perovskite material evidences a multiferroic feature. Ab initio calculations of density of states and band structure for this manganite-like material were carried out by means of the Density Functional Theory and the Linearized Augmented Plane Waves method for both spin orientations. For calculations, the exchange and correlation potentials were included through the local density LDA+U approximation. Density of states study was carried out considering both up and down spin polarizations by the Generalized Gradient Approximation (GGA). Results of total and partial density of states reveal the insulator character of this material with effective magnetic moment 3.3 uB.